2017
DOI: 10.1002/jcb.26348
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐vesicles derived from human Wharton's Jelly mesenchymal stromal cells mitigate renal ischemia‐reperfusion injury in rats after cardiac death renal transplantation

Abstract: The purpose of the present study was to investigate the possible therapeutic effects of the human Wharton-Jelly mesenchymal stromal cells derived micro-vesicles (hWJMSCs-MVs) on renal ischemia-reperfusion injury (IRI) after cardiac death (CD) renal transplantation in rats. MVs were injected intravenously in rats immediately after renal transplantation. The animals were sacrificed at 24 h, 48 h, 1 and 2 weeks post-transplantation. ELISA was used to determine the von Willebrand Factor (vWF), tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Whereas all the studies mentioned above evaluated classical ischemic damage in models of renal artery clamping, Wu and co-workers tested for the first time the effect of EVs in a rat model of IRI after DCD renal transplantation [67]. The authors confirmed that Wharton's jelly MSC-EVs, intravenously injected after renal transplantation, mitigated renal damage, improving survival and function.…”
Section: Evs For Kidney Transplantmentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas all the studies mentioned above evaluated classical ischemic damage in models of renal artery clamping, Wu and co-workers tested for the first time the effect of EVs in a rat model of IRI after DCD renal transplantation [67]. The authors confirmed that Wharton's jelly MSC-EVs, intravenously injected after renal transplantation, mitigated renal damage, improving survival and function.…”
Section: Evs For Kidney Transplantmentioning
confidence: 93%
“…The authors confirmed that Wharton's jelly MSC-EVs, intravenously injected after renal transplantation, mitigated renal damage, improving survival and function. In particular, MSC-EVs were shown to reduce cell apoptosis and inflammation, to stimulate HGF production, and subsequently to alleviate fibrosis [67].…”
Section: Evs For Kidney Transplantmentioning
confidence: 99%
“…Murine studies in which MSC-EVs were employed as a therapeutic tool for IRI are summarized in Table 4 (166,177,(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194). In all of them, administration of MSC-EVs improved renal function and/or decreased tubular injury through multiple mechanisms (164).…”
Section: Extracellular Vesicles As a Therapeutic Tool In Renal Transpmentioning
confidence: 99%
“…Increased proliferation of renal tubule epithelial cells (190) Rat adipose tissue Inhibition of oxidative stress, apoptosis, renal fibrosis (191) Human umbilical cord Increased proliferation and fibrosis (releasing from G2/M cell cycle arrest) (192) Human bone marrow Inhibition of apoptosis (downregulation of Sema3A expression and activation of AKT/ERK pathways through miR-199a-3p); inhibition of NK (193) Human umbilical cord Inhibition of apoptosis, increased proliferation of renal tubule epithelial cells; reduced CD68+macrophages infiltration; reduced fibrosis (decreased expression of aSMA and TGFβ; increased expression of HGF) (194) Human BM Suppression of endoplasmic reticulum stress (miR-199a-5p)…”
Section: Mesenchymal Stromal Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…Several preclinical studies have shown that the administration of exogenous MSCs prevents kidney damage and promotes kidney recovery through a complex series of mechanisms, particularly via the regulation of the immune system and release of paracrine factors and MVs ( Wu et al, 2018 ).…”
Section: Mechanisms Of Msc Involvement In the Improvement Of Renal Pamentioning
confidence: 99%